PENGARUH TEKANAN KERJA BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DAERAH KOTA PAREPARE - Rasmi, Rasmi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine how much influence work pressure, workload, and work environment have on employee performance at the Regional Secretariat of Parepare City. This research was conducted at the Regional Secretariat of Parepare City using Multiple Linear Regression analysis. The method used is a quantitative method with a questionnaire method with a sample size of 36 employees at the Regional Secretariat of the City of Parepare. Based on the results of the research conducted, it shows that: 1) Work pressure has a significant effect on employee performance at the Regional Secretariat of the City of Parepare, showing the t value = 2.092 with a significant value of 0.044. By using t table = 1.665 then t count > t table 2.092 so that the hypothesis is accepted. 2) Workload has a significant effect on employee performance at the Regional Secretariat of Parepare City, showing the calculated value of t = 2.162 with a significant value of 0.000. By using t table = 1.665 then the value of t count > t table 2.162 > 1.665 so that the hypothesis is accepted. 3) The work environment affects the level of employee performance at the Regional Secretariat of the City of Parepare, showing the t value = 4.430 with a significant value of 0.000. By using t table = 1.665 then t count > t table 4.430 > 1.665 so that the hypothesis is accepted